2017
DOI: 10.1016/j.jaip.2016.12.003
|View full text |Cite|
|
Sign up to set email alerts
|

Making the Most of In Vitro Tests to Diagnose Food Allergy

Abstract: Various in vitro tests assess different aspects of the underlying immune mechanism of IgE-mediated food allergy. Some can be used for diagnostic purposes; specific IgE to allergen extracts is widely available; specific IgE to allergen components is used in most specialist centers, and the basophil activation test is becoming increasingly used clinically. IgE to allergen peptides, T-cell assays, allergen-specific/total IgE ratios, and allergen-specific IgG4/IgE ratios are currently reserved for research. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 131 publications
(148 reference statements)
2
72
0
3
Order By: Relevance
“…However, they advised that previously avoided tree nuts should be introduced with caution as there may be other allergens not tested thus there was a chance of a potentially severe allergic reaction. Although diagnostic food challenges were not performed to the tree nuts in this study, previous studies suggest a higher probability of a negative challenge with negative IgE to seed storage proteins . However, due to pollen‐food syndrome, localised symptoms may develop.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, they advised that previously avoided tree nuts should be introduced with caution as there may be other allergens not tested thus there was a chance of a potentially severe allergic reaction. Although diagnostic food challenges were not performed to the tree nuts in this study, previous studies suggest a higher probability of a negative challenge with negative IgE to seed storage proteins . However, due to pollen‐food syndrome, localised symptoms may develop.…”
mentioning
confidence: 89%
“…Although diagnostic food challenges were not performed to the tree nuts in this study, previous studies suggest a higher probability of a negative challenge with negative IgE to seed storage proteins. 3 However, due to pollen-food syndrome, localised symptoms may develop.…”
mentioning
confidence: 99%
“…Activated basophils are important biomarkers of allergic responses, reflecting specific IgE functional activity. In vitro basophil activation tests (BAT) may be useful in monitoring patients on AIT, by ex vivo measurements of CD63 or CD203c expression, basophil histamine release (BHR) or diamine oxidase (DAO), avoiding the risk of severe allergic reactions with in vivo allergen challenge . However, advances in practical aspects of the test are required for standardization and adaptation for use in routine laboratories.…”
Section: Candidate Biomarkers For Immune Monitoring In Allergen Immunmentioning
confidence: 99%
“…Information that can be obtained from sequence analysis is highlighted vivo allergen challenge. [94][95][96][97] However, advances in practical aspects of the test are required for standardization and adaptation for use in routine laboratories. Due to their sequestration into tissues, mast cells remain difficult to investigate in the context of AIT and immune monitoring.…”
Section: Immunoglobulin Transcriptsmentioning
confidence: 99%
“…Although some risk factors related to the severity of FA have been identified, no clear bio‐markers are available to predict the risk or the level of ED in real life or during an OFC. Studies have shown contradictory results about sIgE and SPT and individual risk assessment . Shreffler et al.…”
Section: Food Allergy Biomarkers Attached To Phenotypesmentioning
confidence: 99%